Increasing the Income of Chili Farmers by Implementation of Internal Company Institution - Dwi Kristiana; Mukson Mukson; Siswanto Imam Santoso (The University of Lampung, 2025)
Chili is an important commodity for daily consumption, and its demand has the potential to increase as the population grows. The centralized location of production and the uncertainty of production quantities cause price disparities, reflecting poor supply management. This study aims to describe the corporate institutions of chili farming, analyze institutional performance, and factors that affect income of farmers. The method used is descriptive quantitative with a sample of 77 respondents taken with the Slovin formula at Gapoktan Bina Tani and Gapoktan Sumber Jaya in Blora. Data were collected through interviews with questionnaires, and multiple linear regression analysis was used to determine influential factors. The results showed that the institutional strengthening program variable (X1), the partnership expansion program (X2), and the economic scale improvement program (X3) had a high average value, meaning that the majority of respondents gave positive responses to the programs implemented. Factors that have a significant effect on chili farming income are variables of education level, length of farming, and amount of production, while variables of age, land area, and company performance have no significant effect on chili farming income. This conclusion indicates the need for institutional development to improve the welfare of chili farmers. Keywords: Chilli, Corporation, Farmer, Income, Institution.